Determining nursing students’ attitudes towards, readiness for, expectations from, and satisfaction with distance education and their sense of alienation from their university - Oztas, Duygu; Toru, Fadime; Akgun, Senay; Ozpulat, Funda (Journal of the Pakistan Medical Association, 2024)
Objective: To determine nursing students’ views on attitudes towards distance education during coronavirus disease 2019 pandemic. Methods: The analytical, cross-sectional study was conducted in May and June 2022 at a state university in the Mediterranean region of Türkiye, and comprised nursing students. Data were collected using the Attitude Towards e-Learning Scale, e-Readiness for e-Learning and Expectations Scale, e-Satisfaction Scale, and University Alienation Scale. Data were analysed SPSS 26. Results: Of the 322 participants, 213 (66.1%) were females, and 159 (49.4%) were staying in hostel dormitories. The mean age of the sample was 20.36±1.63 years. There was a significant, moderate and positive correlation between the students’ scores from with respect to readiness, satisfaction, transmission, practicality and content of distance learning (p<0.05). There was a significant, weak and positive correlation of readiness with the education process, interaction and assessment values (p Less-Than Or Equal To 0.05). Conclusion: Alienation towards university education increased in relation to technology skills. Key Words: Distance education, University students, COVID-19 pandemic.